2001
DOI: 10.1046/j.1523-1755.2001.059003959.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of osteopontin in gentamicin-induced acute tubular necrosis and its recovery process

Abstract: These results suggested that OPN is related to the proliferation and regeneration of tubular epithelial cells after tubular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…As described previously [9], renal proximal tubular necrosis appeared to develop on day 6 (day 1–5 administration of gentamicin) in the gentamicin group. On day 10, there was a lot of desquamated epithelial cell debris in the dilated tubular lumens.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…As described previously [9], renal proximal tubular necrosis appeared to develop on day 6 (day 1–5 administration of gentamicin) in the gentamicin group. On day 10, there was a lot of desquamated epithelial cell debris in the dilated tubular lumens.…”
Section: Resultssupporting
confidence: 74%
“…Our previous study showed the up-regulated expression of CD44 in renal tubules during the recovery process after acute tubular necrosis (ATN) [9], but the exact localization and distribution of CD44 during the process of injury and repair of the kidneys remains poorly understood. In this study, we used a gentamicin-induced ATN and spontaneous recovery model in rats and two distinct antibodies, an anti-rat distal extracellular domain (OX49) of standard CD44 (CD44-OX49) and an anti-rat CD44 cytoplasmic tail (CD44CPT), surveyed the different localization of CD44-OX49 and CD44CPT in the surface membranes of renal tubular epithelial cells in different recovery stages after ATN and discussed the potential roles of CD44 localized on different surface membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization with rat SM22α cRNA was conducted as previously described [22]. For digoxigenin-labeled probe synthesis, in vitro transcription was performed using a Dig RNA labeling kit (SP6/T7; Roche).…”
Section: Methodsmentioning
confidence: 99%
“…OPN, a secreted glycoprotein, has been demonstrated to be expressed in normal renal tissues, however, is induced in abnormal kidneys. Though a number of studies [19] have explored the role of OPN in renal diseases, direct evidence on its role in renal injury has not been described. Moreover, very little information is available on human renal disease states and the role of OPN in drug-induced nephrotoxicity in transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of experimental models, expression of OPN is highlighted in these cells. Xie et al [19] suggested that OPN was related to the proliferation and regeneration of tubular epithelial cells after tubular damage. Lewington et al [27] observed that OPN was expressed in regenerating tubules 3 days after induction of acute ischemic injury but not in sham-operated controls.…”
Section: Discussionmentioning
confidence: 99%